MOTIPLAH media implementation to increase reading interest and student learning outcomes - Ria Junita (Eklektika: Jurnal Pemikiran dan Penelitian Administrasi Pendidikan, 2022)
Based on the problems obtained in the initial observations and interviews, the researcher offers the Implementation of MOTIPLAH Media with the aim of describing the implementation of MOTIPLAH media to increase rea dinginterest and student learning outcomes. The type of research used in this study is Classroom Action Research (CAR) whose solution stages refer to Kurt Lewin’s views, namely planning, action, observation and reflection. The data collection techniques used in this study were observation, evaluation tests and documentation. The result of the first cycle research obtained that there were 8 students who completed and as many as 26 students did not complete. The total score obtained from 34 students is 1.850 with the lowest score is 5 and the highest score is 90, the average value is 54,4 and classical student learning completeness is 23,5%. In the second cycle of research, there were 27 students was 2.600 with the lowest score being 30 and the highest score being 95, the average score being 78 and classical student learning completeness was 81,8%. The result of the analysis of student reading interest showed that the number of students who completes the minimum criteria for high reading interest were 36 students with a total score of 2.397 with an average value of 83,3, this indicates that success has been achieved in accordance with the success indicators.